1988
DOI: 10.1002/ajim.4700140404
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among workers at a nuclear fuels production facility

Abstract: A retrospective cohort mortality study was conducted in a population of workers employed at a facility with the primary task of production of nuclear fuels and other materials. Data for hourly and salaried employees were analyzed separately by time period of first employment and length of employment. The hourly (N = 6,687 with 728 deaths) and salaried (N = 2,745 with 294 deaths) employees had a mortality experience comparable to that of the United States and, in fact, exhibited significant fewer deaths in many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 12 publications
1
42
0
1
Order By: Relevance
“…'4 Studies of cancer in workers in the nuclear industry have tended to focus on its relation to the dose of external radiation, and most workforces have experienced a small and generally non-significant increase in overall mortality from prostatic cancer." [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The only other study which examined potential exposure to any of the radionuclides identified here found an increase in mortality from prostatic cancer in men who had been investigated for possible exposure to 3H and who had received high doses of external radiation at the Atomic Weapons Establishment, Aldermaston. "5 Workers from the Savannah River Plant in the United States, which contains five reactors and two heavy water manufacturing plants, did not experience an overall increase in prostatic cancer, but no separate data were given for employees exposed to specific radionuclides.2' There is a need for detailed analyses of risk of prostatic cancer in other workforces of the nuclear industry focused directly on people exposed to the radionuclides identified here.…”
Section: Discussion Iionaftermentioning
confidence: 99%
“…'4 Studies of cancer in workers in the nuclear industry have tended to focus on its relation to the dose of external radiation, and most workforces have experienced a small and generally non-significant increase in overall mortality from prostatic cancer." [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] The only other study which examined potential exposure to any of the radionuclides identified here found an increase in mortality from prostatic cancer in men who had been investigated for possible exposure to 3H and who had received high doses of external radiation at the Atomic Weapons Establishment, Aldermaston. "5 Workers from the Savannah River Plant in the United States, which contains five reactors and two heavy water manufacturing plants, did not experience an overall increase in prostatic cancer, but no separate data were given for employees exposed to specific radionuclides.2' There is a need for detailed analyses of risk of prostatic cancer in other workforces of the nuclear industry focused directly on people exposed to the radionuclides identified here.…”
Section: Discussion Iionaftermentioning
confidence: 99%
“…Workers without complete information on name, SSN, date of birth, and date of first hire were excluded. This cohort of workers expands upon the cohort examined by Cragle et al (1988Cragle et al ( , 1998 by including white males hired between 1975 and 1986 and by including white females and non-white males and females.…”
Section: Methodsmentioning
confidence: 99%
“…Dosimetry information for an additional 1058 workers was identified and computerized during the course of an epidemiological cohort study of SRS workers conducted by Oak Ridge Associated Universities; we refer to this as the SRPABST file. The previous epidemiological analyses of radiation-mortality associations among SRS workers reported by Cragle et al (1998) utilized information from the HPAREH, Fayerweather, and SRPABST files. For the sake of consistency with contemporary nomenclature, dose estimates that were originally expressed in units of rem are discussed and reported in this article in units of sievert (Sv), where 1 Sv ¼ 100 rem.…”
Section: Computerized Radiation Dosimetry Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…La revue des quatre études américaines considérées dans le cadre du projet a démontré une corrélation positive entre la mortalité par leucémie et une exposition à un rayonnement ionisant de faible intensité en milieu de travail (Cragle et al, 1988(Cragle et al, , 1998Schubauer-Berrigan et al, 2007 ;Richardson et Wing, 2007). Ici encore, il est difficile de tirer une quelconque conclusion quant au risque associé à une exposition au tritium seul.…”
Section: éTudes éPidémiologiques Sur Des Travailleurs Exposés Au Rayounclassified